Government of Jammu and Kashmir Draft Sixth Five Year Plan (1980-85) and Annual Plan (1981-82) Volume XIII Leh District - Planning Commission (Planning Commission, 1980)
It is on established fact that overall Power Position in India as of a whole is quite unsatisfactory as present. Most of the states in the country are facing power shortage. The overall generation and power availability is not keeping pace with the demand. Such a situation if allowed to continue for long is apt to prove detrimental to the country and needs to be arrested forthwith, The Centre and the state Government are conscious of it and concerted efforts are being put in at all levels to bridge the gap between the power availability and its demand. In order to facilitate the study, analyze the problems and examine the same for concrete results, the Central Electricity Authority, Ministry of Energy, Government of India has divided the country in four Regions and Regional Electricity Boards have been formed for review.
Government of Jammu and Kashmir
Planning and Development Department Srinagar
Keywords: Power; Reorganization of power Development Department; New Schemes Proposed For Investigations; Large and Medium Industries; Village and Small Scale Industries; Mining Mineral Development; Handicraft Sector; Administrative Division; Supply and Stores Division; District Level Administration; Exhibition and Publicity Division